Information technology for learning organisations and lifelong learning - Dovedan Han, Zdravko (Array, 1999)
Line of investigation included in the project led to questions about the modern technology of education or educational technology consistency with the idea and practice of the permanent education concept. We should view the process of lifelong learning as a continuum where the traditional education takes a new form through the usage of new media thus becoming widely accessible to everyone with Internet access and need for education in any moment of his/her life. The limiting factor for the proper usage of Internet in classroom in Croatia is lack of the national education packages available on the net. While waiting for our own projects to develop we could already use some Internet resources such as foreign language courses. The authors underlined the need for internationally acceptable programs, which would include not only the skills required to use new information technologies, but also the knowledge on how to create new information products with added value and such knowledge and skills which would ultimately enable students to accept new and nontraditional jobs.